2020
DOI: 10.1177/1753193420963255
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical fixation of a cementless conical cup in cortical versus cancellous trapezial bone: an experimental study

Abstract: In a pig bone model mimicking the human trapezium, we assessed the cementless fixation of trapezial cups in cancellous and cortical bone. Thirty-two saddle-shaped pig forefoot bones were prepared for cup fixation. Conical Konos cups (Beznoska, Kladno, Czech Republic) size 9 mm or 10 mm diameter were impacted. Cup migration was evaluated with repeated radiostereometry after intervals of cyclic-load tests. Migration increased for every load-interval up to 750 N and was higher with cancellous bone fixation than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Furthermore, for a larger cup diameter, the surface area of the Moovis cups has a greater percentage increase compared to the Type T cup. An experimental study of the conical Konos cup (Beznoska, Kladno, Czech Republic) inserted with cortical bone rim fixation showed that the risk difference for failure was 63% in favor of 10 mm cups compared to 9 mm cups [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, for a larger cup diameter, the surface area of the Moovis cups has a greater percentage increase compared to the Type T cup. An experimental study of the conical Konos cup (Beznoska, Kladno, Czech Republic) inserted with cortical bone rim fixation showed that the risk difference for failure was 63% in favor of 10 mm cups compared to 9 mm cups [28].…”
Section: Discussionmentioning
confidence: 99%
“…For conical cups, the surface area and cup diameter have been shown to affect the primary mechanical stability and load tolerance after press-fit fixation in bone [28]. Considering the same cup diameter of conical cups and hemispherical cups, the surface area is smaller for hemispherical cups [28]. Therefore, the postoperative load tolerance until achievement of secondary osseointegration is likely higher for conical cups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). The central hard subchondral bone of the distal articular surface of the trapezium should be preserved because it improves the mechanical fixation of a cementless cup ( 37 ).
Figure 2 Removal of the medial and lateral osteophytes at the distal articular surface of the trapezium.
…”
Section: Surgical Techniquementioning
confidence: 99%
“…Fixation in cancellous bone has been shown to be worse compared with cortical bone in a recent experimental study using porcine bone. 19 Combined with a reduced contact area between the prosthesis and the surrounding bone, especially in osteoporotic bone, this may lead to suboptimal fixation of the prosthesis, potentially affecting the long-term implant survival.…”
Section: Introductionmentioning
confidence: 99%